Analisis Minat Belajar Siswa Broken Home dan Strategi Penanganannya - Salsabila, Putri; Saman, Abdul; Amirullah, Muhammad (Universitas Negeri Makassar, 2025)
This study examines the learning interests of students from broken homes and how they are handled at a vocational high school in Soppeng. The objectives of this study are to: (1) describe the learning interest of student AIS, (2) identify the factors that influence AIS’s learning interest, and (3) explain the efforts made to address AIS’s learning interest issues. This study uses a qualitative approach with a case study design. The subject is one student, referred to as AIS. Data collection techniques include interviews, observation, and documentation. Data analysis involves data reduction, data presentation, and drawing conclusions. The results show that: (1) AIS’s learning interest is categorized as low, indicated by frequent school absences, tardiness, lack of enthusiasm, indifference to lessons, and rarely completing assignments. (2) The factors contributing to AIS’s low learning interest include a lack of intrinsic motivation, limited parental support, and emotional neglect following the death of AIS’s mother. (3) The intervention to address AIS’s low learning interest was carried out through reality counseling using the WDEP system, consisting of four stages: exploring Wants, Doing, self-Evaluation, and Planning.